Beyond Religious Boundaries: Determinants Driving Non-Muslim Consumers’ Halal Product Choices in Palu, Indonesia - Syamsu, Nur; Aisya, Sitti; MD, Muthmainnah; Fitriani, Nur; Ikhram, M.; Ismail, Nurizal (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2025)
Purpose: This study aims to identify the key factors influencing non-Muslim consumers’ preferences for halal food products in Palu, Indonesia, focusing on knowledge, attitudes, pricing, accessibility, social influence, trust in certification, and consumption experience..Design/methodology: A quantitative, cross-sectional survey was conducted with 117 non-Muslim respondents in Palu. Data were collected using a structured questionnaire adapted from validated instruments and analyzed using SPSS (version 29). The analysis involved descriptive statistics, validity and reliability testing, classical assumption tests (normality, multicollinearity, heteroscedasticity), and multiple linear regression with t-test and F-test to examine the relationships between variables and purchasing decisions.Findings: The results reveal that knowledge negatively influences purchasing decisions, whereas positive attitudes, accessibility, social influence, trust in halal certification, and consumption experience significantly enhance the likelihood of choosing halal products among non-Muslim consumers.Practical Implication: The findings suggest that marketers should reframe halal knowledge into practical benefits (health, hygiene, quality), improve accessibility, strengthen social engagement, and enhance trust through credible certification to increase adoption among non-Muslim consumers.Originality/Value: This study integrates consumer behavior theory, the Theory of Planned Behavior, and post-disaster consumer dynamics to explain halal consumption among non-Muslims in a multicultural setting, using a rigorous SPSS-based analytical approach.